2019
DOI: 10.3390/ani9121003
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dietary Replacement of Fish Meal with Whey Protein Concentrate on the Growth Performance, Fish Health, and Immune Status of Nile Tilapia Fingerlings, Oreochromis niloticus

Abstract: The present study was conducted to assess the effect of replacing fish meal with whey protein concentrate (WPC) on the growth performance, histopathological condition of organs, economic efficiency, disease resistance to intraperitoneal inoculation of Aeromonas hydrophila, and the immune response of Oreochromis niloticus. The toxicity of WPC was tested by measuring the activity of caspase 3 as an indicator of cellular apoptosis. Oreochromis niloticus fingerlings with average initial weight 18.65 ± 0.05 gm/fish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 70 publications
(74 reference statements)
1
23
0
Order By: Relevance
“…Increased surface area for the absorption, improved feed digestion, nutrient utilization, and defense against pathogens by mucin layers on the intestinal mucosa were, therefore, substantiated by these findings, which in turn reflected the effect on the fish growth performance as reported by Reference [57]. The digestive and absorptive capacity of the fish is estimated by the effective indicators, including the numbers of goblet cells (mucus-secreting cells) and the intestinal villous heights [16,58,59]. Defense against foreign antigens is attributed to IEL, effective components of gut-associated lymphoid tissue [60].…”
Section: Discussionmentioning
confidence: 61%
“…Increased surface area for the absorption, improved feed digestion, nutrient utilization, and defense against pathogens by mucin layers on the intestinal mucosa were, therefore, substantiated by these findings, which in turn reflected the effect on the fish growth performance as reported by Reference [57]. The digestive and absorptive capacity of the fish is estimated by the effective indicators, including the numbers of goblet cells (mucus-secreting cells) and the intestinal villous heights [16,58,59]. Defense against foreign antigens is attributed to IEL, effective components of gut-associated lymphoid tissue [60].…”
Section: Discussionmentioning
confidence: 61%
“…Pseudomonas septicemia is considered a critical fish disease, causing high mortality rates and economic losses among freshwater fishes [65]. The challenge test is used as an ultimate assay to assess the fish immune response [66][67][68][69][70][71]. The results displayed an increase in the survivability of fish fed a SYN diet following challenge with P. aeruginosa, indicating improvement of the immunity of fish fed a diet complemented with synbiotic and a competitive efficiency against pathogenic bacteria [40,41] as previously proven by the enhancement of several immunological markers.…”
Section: Discussionmentioning
confidence: 99%
“…One of the greatest impacts of replacement studies is the improvement of economic visibility of the diet, among other goals. Several alternatives have been used in partial replacement of FM and reduce feed costs, including high protein distillers dried grains [66,67], meat and bone meal [68], silkworm (Anaphe infracta) [69], insect meal [70], animal by-products [70], and whey protein [71]. Interestingly, the findings of the present study revealed the success of total replacement of FM with ZBM regarding the zootechnical performance and economic benefit by considering the natural collection of ZBM.…”
Section: Discussionmentioning
confidence: 57%